2017
DOI: 10.1016/j.jsxm.2017.11.227
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Analysis of Psychosocial Factors of Sexual Desire in Men

Abstract: Background The literature lacks studies of the male sex drive. Most existing studies have focused on hypoactive sexual desire disorder in coupled heterosexual men, highlighting some of the main related biological, psychological, and social factors. Aim To evaluate the role of selected psychological and social variables affecting male sexual desire such as quality of life, sexual function, distress, satisfaction, psychological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 68 publications
1
23
0
Order By: Relevance
“…Negative emotions affect sexual functioning negatively [45]. Additionally, it has been reported in the literature that people with sexual dysfunction have higher levels of alexithymia [61]. In this study, it was found that those with decreased sexual functioning during the COVID-19 pandemic had higher levels of alexithymia, anxiety, and depression than those who did not.…”
Section: Alexithymia Anxiety and Depression Levels With A Change In Sexual Functioningsupporting
confidence: 48%
See 1 more Smart Citation
“…Negative emotions affect sexual functioning negatively [45]. Additionally, it has been reported in the literature that people with sexual dysfunction have higher levels of alexithymia [61]. In this study, it was found that those with decreased sexual functioning during the COVID-19 pandemic had higher levels of alexithymia, anxiety, and depression than those who did not.…”
Section: Alexithymia Anxiety and Depression Levels With A Change In Sexual Functioningsupporting
confidence: 48%
“…Psychological factors affect people's sexual health and behavior. It is stated in the literature that anxiety and depression affect the decrease in sexual desire [60,61]. Negative emotions affect sexual functioning negatively [45].…”
Section: Alexithymia Anxiety and Depression Levels With A Change In Sexual Functioningmentioning
confidence: 99%
“…Conversely, it should be noted that the will to adhere to stereotypic gender roles of the identified gender may also influence the expression of sexual desire and behavior in transgender people. For example, some FtM may report higher desire levels to show more masculine and virile attitudes and behavior [31,32].…”
Section: Transgender Women and Menmentioning
confidence: 99%
“…Psychological factors, specific mood states can inhibit sexual desire. Depression and anxiety have been mostly associated with low levels of desire (6,7). Those who live a stable relationship but are not living together, on the contrary, have a strong desire for the other, who however cannot be satisfied for the physical distance and the impossibility of approaching due to the restriction in the movements of people imposed by the State.…”
Section: Introductionmentioning
confidence: 99%